EVALUATING BAWASLU’S SiGapLapor FOR ELECTORAL JUSTICE IN INDONESIA’S 2024 ELECTION - Hidayat, Nur; Muhtar, Muhtar (JWP (Jurnal Wacana Politik), 2026)
This article assesses the effectiveness of the Election Violation Handling and Reporting Information System (SiGapLapor) operated by Indonesia’s Election Supervisory Body (Bawaslu) as a case of digitalising electoral oversight. Using a qualitative-exploratory case study, the research draws on document analysis (regulations, internal reports, and SiGapLapor web statistics) and semi-structured interviews and focus group discussions with election supervisors and ICT managers. Findings indicate that SiGapLapor works reasonably well as an administrative registry and an internal reporting tool, but remains weak as a participatory public complaints mechanism and as an instrument of electoral justice. Key constraints include a non-user-centred interface, predominantly manual verification, uneven local infrastructure and human capacity, and limited system integration and data openness. The article proposes three development agendas for the 2029 election cycle: a citizen-centric redesign grounded in Digital-Era Governance, stronger case-tracking features with integration and Open Government Data interoperability, and an explicit public value orientation through co-creation and institutional capacity building within Bawaslu.